Pengaruh Perbedaan Tegangan Pemanas terhadap Performa Refrigeran R12, R134a dan MC134 pada Refrigeration Laboratory Unit - Senoadi, Senoadi; Aliandi, Arif Akhmad; Permatasari, Rosyida (MESIN, 2019)
Along with technological developments and population growth, the need for air conditioner (AC) is increasing, both those used in industry, offices, buildings, housing, vehicles, and others. In the use of AC, refrigerant is needed. Based on the Montreal agreement, it was agreed to replace refrigerants that are more environmentally friendly. The refrigerant used today is refrigerant with CFC and HCFC compounds. The use of those refrigerants result in ODP and GWP. This study aims to determine the energy efficiency of three refrigerants: R12, R134a, and MC134, by comparing the COP value of a refrigeration laboratory unit machine. Based on the test results, COP of MC134 refrigerant has the highest value compared to R12 and R134a refrigerants. Therefore, it can be concluded that MC134, a hydrocarbon refrigerant, could be considered as a substitute for R12 and R134 refrigerants, eventhough  flammability of the  hydrocarbons at certain temperatures should be considered also.